2019
DOI: 10.1021/acsomega.9b01508
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Amorphous Silicas Hydrophobized by Various Pathways

Abstract: Various nanostructured amorphous silicas [fumed silicas such as crude (A-300), hydro-compacted (cA-300, TS 100), and precipitated silica Syloid 244] were modified by different polydimethylsiloxanes such as PDMS5, PDMS100, PDMS200, PDMS1000, and PDMS12500 (the label numbers show the viscosity (η) values) using dimethyl carbonate (DMC) as a siloxane-bond-breaking reagent. In addition, hexamethyldisilazane was used to modify fumed silica cA-300. The nanocomposites were characterized using microscopy, infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Among MPSs, only a limited number of studies can be found on hydrophobized Syloid-based drug delivery systems [30,31], even though these materials have highly developed mesoporous networks and a large surface area. Moreover, these systems are ideal to adsorb a remarkable amount of API.…”
Section: Introductionmentioning
confidence: 99%
“…Among MPSs, only a limited number of studies can be found on hydrophobized Syloid-based drug delivery systems [30,31], even though these materials have highly developed mesoporous networks and a large surface area. Moreover, these systems are ideal to adsorb a remarkable amount of API.…”
Section: Introductionmentioning
confidence: 99%
“…Linear organosiloxanes are generally not considered to be reactive with inorganic oxide surfaces, and enormous efforts have been made over the last 50 years to develop silicon-containing reagents with reactive functional groups [ 42 ]. Previously, it was found that dimethyl carbonate (DMC) [ 43 ], which is an environmentally friendly reagent [ 44 , 45 , 46 ], can promote partial depolymerization of organosiloxanes (e.g., polydimethylsiloxane, PDMS) and breakage of the siloxane bonds in a surface layer of silica nanoparticles. These reactions allow the silica surface hydrophobization by PDMS fragments under relatively mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was based on a blend of Kelvin and modified BET equations [46][47][48] (MND method) that was used in the SCV/SCR method with models of slit-shaped and cylindrical pores and voids between spherical nanoparticles (SCV model) [43][44][45]. Note that the SCR procedure was also successfully applied to analyze the SAXS data to compute the particle size distributions with models of spherical, lamellar, and cylindrical particles [49][50][51]. However, the MND method has some disadvantages.…”
Section: Introductionmentioning
confidence: 99%